Does Your Business Process Management (Still) Fit the Market? – A Dynamic Capability Perspective on BPM Strategy Development - Niehaves, Björn; Plattfaut, Ralf; Becker, Jörg (16th Americas Conference on Information Systems (AMCIS), 2010)
Business Process Management (BPM) can be viewed as a set of techniques to integrate, build, and reconfigure an organization‟s business processes for the purpose achieving a fit with the market environment. While business processes are rather stable in low-dynamic markets, the frequency, quality, and importance of business process change amplifies with an increase in environmental dynamics. Taking the public sector example, we recognize that market dynamics can change over time (market dynamic shift), here: increase. We show that existing designs of BPM might not be able to cope with the mounting frequency and quality of business process change (market-BPM-misfit). On the basis of a qualitative in-depth case study, we provide evidence that a major cause for such misfit lies in ineffective (second order) organizational learning. We contribute to the literature by applying the Resource-Based View and Dynamic Capability framework to the case of BPM in order to better understand shifts in market dynamics and their consequences for BPM effectiveness. Practitioners find a proposal for identifying, understanding, and reacting to a market-BPM-misfit and for developing market-oriented BPM strategy.